Experimental model of cultured keratinocytes Modelo experimental de cultura de queratinócitos - Alfredo Gragnani (Acta Cirurgica Brasileira, 2003)
The bioengineering research is essential in the development of ideal combination of biomaterials and cultured cells to produce the permanent wound coverage. The experimental model of cultured keratinocytes presents all steps of the culture, since the isolation of the keratinocytes, preparation of the human acellular dermis, preparation of the composite skin graft and their elevation to the air-liquid interface. The research in cultured keratinocytes model advances in two main ways: 1. optimization of the methods in vitro to the skin cells culture and proliferation and 2. developing biomaterials that present similar skin properties. A pesquisa em bioengenharia é primordial no desenvolvimento da combinação ideal de biomateriais e células cultivadas para produzir a cobertura definitiva das lesões. O modelo experimental da cultura de queratinócitos apresenta toda as etapas do cultivo, desde o isolamento dos queratinócitos, preparação da derme acelular humana, do enxerto composto e da sua elevação à interface ar-líquido. A pesquisa em modelo de cultura de queratinócitos desenvolve-se em duas vias principais: 1. otimização dos métodos in vitro para cultivo e proliferação de células da pele e 2. desenvolvimento de biomateriais que mimetizem as propriedades da pele.